STRATEGIC USE OF DIGITAL MARKETING TO BOOST BRAND AWARENESS IN CREATIVE AGENCIES: THE CASE OF ALICYART STUDIO, JAKARTA - Rania Alicya; Nila Armelia Windasari (RADJA PUBLIKA, 2026)
Alicyart Studio, a creative agency based in Jakarta, Indonesia has been experiencing low brand awareness on its Instagram account. This purpose of this study is to find strategic recommendation to enhance Alicyart Studio’s brand awareness using digital marketing. There several factors on why Alicyart Studio is experiencing this issue are inconsistent posting schedule, the absence of paid digital advertising, and an unclear marketing communication. The low brand awareness affects Alicyart Studio’s revenue because it limits Alicyart Studio’s ability to attract new potential clients and compete in Jakarta’s creative agency market. This research aims to identify the key factors that contribute to the low brand awareness, as well as finding strategic digital marketing approach that is suitable to be implemented by Alicyart Studio or other small creative agencies in Jakarta. An interrupted time series using quasi-experimental research design was conducted to evaluate Alicyart Studio’s Instagram performance and changes in the audience perception during the pre-treatment (baseline) and post-treatment periods. The experiment lasts for four weeks to test which content pillars (functional, emotional, educational, and agile) has the highest performance and each pillar was tested for one week. The key performance indicators include observing the number of reaches, engagement, follower growth, and profile visits. In addition, mixed-method research was conducted by obtaining quantitative and qualitative data. The online survey was conducted twice during both periods with 150 respondents, and is analyzed using descriptive statistical analysis and cross-tabulation. Qualitative data were obtained through semi-structured interview targeting Alicyart Studio’s existing clients, followers, and potential clients during the post-treatment period and were analyzed using thematic analysis. The results show that the educational and functional content pillars are the pillars with the highest performance, while emotional pillar act as a complementary to build brand’s trust. On the other hand, agile content has the lowest impact on Alicyart Studio’s brand awareness since its primary function was only to stay relevant with the current trends. During the implementation of the treatment, this study applied integrated marketing communication, content pillar strategy, and paid digital advertising to improve Alicyart Studio’s brand awareness.